2004
DOI: 10.1044/1092-4388(2004/032)
|View full text |Cite
|
Sign up to set email alerts
|

Input That Contradicts Young Children’s Strategy for Mapping Novel Words Affects Their Phonological and Semantic Interpretation of Other Novel Words

Abstract: Children tend to choose an entity they cannot already label, rather than one they can, as the likely referent of a novel noun. The effect of input that contradicts this strategy on the interpretation of other novel nouns was investigated. In pre- and posttests, 4-year-olds were asked to judge whether novel nouns referred to "name-similar" familiar objects or novel objects (e.g., whether japple referred to an apple or a binder clip). During an intervening treatment phase, they were asked to pick the referents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 33 publications
1
23
1
5
Order By: Relevance
“…Results here, like those of Jarvis et al (2004), suggest that pragmatics influence whether children interpret an accented form as novel or familiar. Perhaps over the longer term, children in multiaccent contexts would become accustomed to familiar-word interpretations of similar variants.…”
Section: Implications For Learning Language With Accent Variabilitymentioning
confidence: 55%
See 1 more Smart Citation
“…Results here, like those of Jarvis et al (2004), suggest that pragmatics influence whether children interpret an accented form as novel or familiar. Perhaps over the longer term, children in multiaccent contexts would become accustomed to familiar-word interpretations of similar variants.…”
Section: Implications For Learning Language With Accent Variabilitymentioning
confidence: 55%
“…This experience might bias them to treat the accented forms in the test phase as further novel words and seek out novel referents, even if they have some awareness of the similarity to the original pronunciations. Jarvis, Merriman, Barnett, Hanba, and Van Haitsma (2004) have shown that young children who are initially guided to select similarly-named familiar objects rather than novel objects for novel words-such as being taught that "plasses" are a type of glasses-make fewer novel-object identifications for further wordlike names, such as inferring than "cardon" refers to a car rather than a novel object. This suggests that pragmatic cues may enhance word generalization to a similar but not-previously experienced word form.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented by these studies 15,[19][20][21] lead us to create hypothesis that the results found in the present study are due to the fact that the instrument used to evaluate the expressive was simpler, in terms of lexical complexity, in relation to the instrument that evaluated the receptive vocabulary, thus favoring RESUMO Objetivo: comparar os índices de vocabulário receptivo e expressivo de crianças com Transtorno Específico do Desenvolvimento da Fala e da Linguagem. Métodos: trata-se de estudo transversal, com amostra constituída por 21 crianças com Transtorno Específico do Desenvolvimento da Fala e da Linguagem, avaliadas em clínica-escola de Fonoaudiologia, sendo 9 crianças do gênero feminino e 12 crianças do gênero masculino, com idades entre 3 e 11 anos.…”
Section: Resultsunclassified
“…Besides that, children present a better performance in tasks of comprehension in relation to tasks of production of new words and are subject to the same principles of acquisition (even though these go through great interference of the abilities of information processing); they are able to map the unknown name to its referential based on their previous knowledge of the category to which the known object belongs to 19 , assuming the principle of mutual exclusiveness (that each object corresponds to a name) when in face of non categorized referentials 15,20 and are influenced by the referential intention of their interspeakers 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation